SIGNALING PATHWAYS IN THE CONTROL OF EMBRYONIC DEVELOPMENT OF THE ENTERIC NERVOUS SYSTEM - Djuknic, Milos; Puskas, Nela; Labudovic Borovic, Milica; Jankovic, Radmila (HEALTH CARE, 2022)
The enteric nervous system (ENS) provides intrinsic innervation of the gastrointestinal tract and is the largest and most complex part of the peripheral nervous system. Its functions are vital for life and include control of motility of the digestive tract, secretion, as well as fluid and electrolyte exchange through the intestinal mucosa. ENS is capable of performing most of these functions completely autonomously. A large number of developmental and genetic studies of the most common congenital disease of the ENS, Hischsprung’ s disease, has made a major contribution to the understanding of the embryonic development of the ENS. ENS cells raise from the vagal (mostly) and sacral region of the neural crest. These precursor cells migrate along the primitive gut in opposite directions, in order to colonize the entire gut. Proliferation, migration, neuro-glial differentiation, and other processes through which precursor cells of the ENS undergo, are regulated by various signaling pathways. Some of the most important molecules that participate in the regulation of the proper development of the ENS are GDNF (Glial Derived Neurotrophic Fatcor) and its receptor RET (REarranged during Transfection), endothelin 3 and its receptor EDNRB (endothelin receptor type B), transcription factors SOX10 (SRY-box transcription factor 10), PHOX2B (Paired-like Homeobox 2B), morphogens such as BMP 2 and 4 (Bone Morphogenic Proteins) and others. Although our knowledge about control of the development of the ENS has increased significantly in recent years, complexity of structure and function of the ENS requires further research. This review summarizes our current understanding of the most important regulatory mechanisms and signaling pathways involved in the development of the ENS.